Decision Support System for Prospective Scholarship Recipients Using SMARTER and Forward Chaining Method - Muhammad Fairuzabadi; Agustia Rizki, Joyanda; Oyama, Sunggito (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2023)
The purpose of this research is to design and build a web-based decision support system application to determine prospective scholarship recipients at MAN 2 Yogyakarta and test its reliability. The Decision Support System is a problem solving system with supporting tools. This system can solve problems using algorithm methods. One of the decision support system methods that can be applied to scholarship cases at MAN 2 Yogyakarta is the Simple Multi-Attribute Rating Technique Exploiting Ranks (SMARTER) method and forward chaining. The SMARTER method is a decision support method by determining the criteria and sub-criteria and their weight using the ROC (Rank Order Centroid). Meanwhile, the forward chaining method is a search method or a forward tracking technique that starts with existing information and combines rules to produce a conclusion or goal. The advantages of the DSS that have been developed are as follows. (1) The DSS built can be used by the scholarship selection team to recommend students who have the potential to get scholarships more quickly and objectively (2) The DSS for prospective scholarship recipients that was developed uses two methods of calculation, namely the Simple Multi-Attribute Rating Technique Exploiting Ranks (SMARTER) and Forward Chaining methods, so that the prediction results are better and faster. The SMART method emphasizes more detailed criteria and the Forward Chaining Method allows for a faster selection process.